Investigation of acute organophosphate poisoning in humans based on sociodemographic and role of neurotransmitters with survival study in South India - Sinha, Sukesh Narayan; Kumpati, Rajesh Kumar; Ramavath, Pandu Naik; Sangaraju, Rajendra; Gouda, Balaji; Chougule, Priyanka (Scientific reports, 2022)
The aim of this study was to investigate the sociodemographic characteristics of patients based on the poison chosen and different types of organophosphorus compounds. The data were collected to explore the sociodemographic characteristics of organophosphate (OP)-poisoned patients based on the source, site, and route of poisoning, education level, occupational status, and the purpose of poisoning. Furthermore, we estimated the serotonin and dopamine levels in the plasma samples of patients, and survival plots were also described. During the study of OP pesticide poisoning in 116 human subjects and 5 healthy volunteers, we observed, based on the survival plot, that75.9% of the patients were discharged, and the remaining patients died (24.1% of the patients) due to respiratory failure followed by cardiac arrest. Our findings suggest that the serotonin levels significantly ( p < 0.01 and p < 0.001) decreased from 12 to 36 h, whereas the dopamine levels slightly increased from 12 to 36 h in the group with OP poisoning compared to the control group. Based on these findings, this study may aid in deciphering the precise mechanism by which pesticides cause behavioural changes that influence serotonin and dopamine levels in OP-poisoned patients. The purpose of this work was to serve as a small reminder of the risk to public health associated with organophosphate pesticides.